Health-Related Quality of Life Instruments for Clinical Trials in AL Amyloidosis: Report from the Amyloidosis Forum HRQOL Working Group - Rizio AA; White MK; D’Souza A; Hsu K; Schmitt P; Quock TP; Signorovitch J; Lousada I; Sanchorawala V (Patient Related Outcome Measures, 2023)
Avery A Rizio,1 Michelle K White,1 Anita D’Souza,2 Kristen Hsu,3 Paula Schmitt,4 Tiffany P Quock,5 James Signorovitch,6 Isabelle Lousada,3 Vaishali Sanchorawala7 1QualityMetric Incorporated, LLC, Johnston, RI, USA; 2Froedtert & MCW Cancer Center, Medical College of Wisconsin, Milwaukee, WI, USA; 3Amyloidosis Research Consortium, Boston, MA, USA; 4Amyloidosis Support Groups, Inc, Wood Dale, IL, USA; 5Prothena Biosciences Inc, South San Francisco, CA, USA; 6Epidemiology and Biostatistics, Analysis Group, Inc, Boston, MA, USA; 7Amyloidosis Center, Boston University School of Medicine and Boston Medical Center, Boston, MA, USACorrespondence: Isabelle Lousada, Amyloidosis Research Consortium, 320 Nevada Street, Suite 210, Newton, MA, 02460, USA, Tel +1 617 467 5170, Email ilousada@arci.orgAbstract: Systemic AL (light chain) amyloidosis is a rare protein misfolding disorder associated with plasma cell dyscrasia affecting various organs leading to organ dysfunction and failure. The Amyloidosis Forum is a public–private partnership between the Amyloidosis Research Consortium and the US Food and Drug Administration Center for Drug Evaluation and Research with the goal of accelerating the development of effective treatments for AL amyloidosis. In recognition of this goal, 6 individual working groups were formed to identify and/or provide recommendations related to various aspects of patient-relevant clinical trial endpoints. This review summarizes the methods, findings, and recommendations of the Health-Related Quality of Life (HRQOL) Working Group. The HRQOL Working Group sought to identify existing patient-reported outcome (PRO) assessments of HRQOL for use in clinical trials and practice deemed relevant across a broad spectrum of patients with AL amyloidosis. A systematic review of the AL amyloidosis literature identified 1) additional signs/symptoms not currently part of an existing conceptual model, and 2) relevant PRO instruments used to measure HRQOL. The Working Group mapped content from each identified instrument to areas of impact in the conceptual model to determine which instrument(s) provide coverage of relevant concepts. The SF-36v2® Health Survey (SF-36v2; QualityMetric Incorporated, LLC) and Patient-Reported Outcomes Measurement Information System-29 Profile (PROMIS-29; HealthMeasures) were identified as instruments relevant to patients with AL amyloidosis. Existing evidence of reliability and validity was evaluated with a recommendation for future work focused on estimating clinically meaningful within-patient change thresholds for these instruments. For sponsors, the context of use—including specific research objectives, trial population, and investigational product under study—should inherently drive selection of the appropriate PRO instrument and endpoint definitions to detect meaningful change and enable patient-focused drug development.Keywords: endpoints, drug development, rare diseases, patient-reported outcome, SF-36v2, PROMIS-29